Studi Perhitungan Volume Bahan Bakar Minyak Menggunakan Metode Perhitungan Liter Standar 15 derajat Celsius Pada Motor Tanker - Tarigan, Kristian; Sitanggang, Hodmiantua; ., Widiyanto; Sholeha, Dewi (Rekayasa Material, Manufaktur dan Energi, 2023)
The method of calculating the volume of fuel oil using standard 15⁰ C is one of the methods used internationally in calculating the volume of handover transactions. To standardize the calculation of fuel volume in various weather conditions, there are several fuel calculation methods, namely the Observed calculation method, th calculation method in standard 15⁰ C, the calculation method in barrels and the calculation method in long tons. For the calculation method that is suitable for use in Indonesia is the standard volume calculation method of 15⁰ C, so that in extreme weather conditions or temperature differences, the volume calculation can still be accommodated even though the difference is very significant. In this case, we take a sample calculation of the volume of MFO fuel oil through the Moto Tanker at the Belawan PLTU Jetty Port. From the measurement results, the overall volume was 4,802,983 liters of Observed, and at a standard volume of 15⁰ C, a volume of 4,747,268 liters of standard 15⁰ C was obtained. From these results, the difference between the Observed volume and the standard volume of 15⁰ C was 55,715 liters or equivalent to 1.16% of the volume Observed. So it can be concluded that the standard volume value of 15⁰ C is 1.16% smaller than the Observed volume and the standard volume of 15⁰ C will always be lower than the Observed volume. For this reason, the standard volume calculation method of 15⁰ C is a very suitable method for calculating the volume of fuel oil.